2014
DOI: 10.1289/ehp.1307044
|View full text |Cite|
|
Sign up to set email alerts
|

Neurodevelopmental Disorders and Prenatal Residential Proximity to Agricultural Pesticides: The CHARGE Study

Abstract: Background: Gestational exposure to several common agricultural pesticides can induce developmental neurotoxicity in humans, and has been associated with developmental delay and autism.Objectives: We evaluated whether residential proximity to agricultural pesticides during pregnancy is associated with autism spectrum disorders (ASD) or developmental delay (DD) in the Childhood Autism Risks from Genetics and Environment (CHARGE) study.Methods: The CHARGE study is a population-based case–control study of ASD, DD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
297
2
16

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 470 publications
(324 citation statements)
references
References 40 publications
9
297
2
16
Order By: Relevance
“…Recent scientific reports has drawn attention and have shown that there is a relation between use of pesticides and neurodevelopmental disorders in children when exposure occur in pre and perinatal periods [22][23][24]. In this sense, a reported passage of both, fipronil and it metabolite fipronil sulfone, through the milk in domestic animals [25] increasing concerns regarding exposure on these critical periods.…”
Section: Introductionmentioning
confidence: 99%
“…Recent scientific reports has drawn attention and have shown that there is a relation between use of pesticides and neurodevelopmental disorders in children when exposure occur in pre and perinatal periods [22][23][24]. In this sense, a reported passage of both, fipronil and it metabolite fipronil sulfone, through the milk in domestic animals [25] increasing concerns regarding exposure on these critical periods.…”
Section: Introductionmentioning
confidence: 99%
“…This delaying childbearing trend contributes around 4.6% increase in autism over the decade. 20 Some researchers found autism risk across generations epigenetically. A statistically significant nonlinear monotonic association was found between grand-paternal advanced age at the time of birth of the parent and autism risk in their grandchildren.…”
Section: Discussionmentioning
confidence: 99%
“…It has been noted that in agricultural areas where the use of pesticides is prevalent, there is a high incidence of metabolic disorders such as diabetes, cardiovascular disease, and obesity [25,26]. Chronic exposures to these mitochondrial inhibitors (pesticides) have also been linked to certain neurologic disorders such as Parkinson's disease and autism [27,28]. Experimental studies have linked chronic exposures of these toxins to the development of specific metabolic disorders.…”
Section: Application Of Cybrids To Toxicologic Poisoningmentioning
confidence: 99%